Computer-aided design of a mass production circuit - Foo, Say Wei (2009)
Tolerance of the circuit components can sometimes bring about costly consequences in mass production. To tackle this problem, recent efforts have been dedicated to develop tolerant circuit design in order to boost manufacturing yield [1]. To redesign a practical circuit successfully, a ombination of many techniques is needed. This paper summarizes the techniques used in the redesigning of a practical mass production circuit that consider all the practical requirements. Experiments show that computer aided design along with tolerance design techniques are valuable tools in mass production.